Advancing social justice and affirming humanity in developmental science research with African American boys and young men. Issue 3 (2nd July 2020) - Smith, Chauncey D.; Smith Lee, Jocelyn R.
Abstract: This commentary engages the three elements of a social justice framework in the study of African American Boys and Men's (AABM) positive development, proposed by Barbarin, Tolan, and Gaylord-Harden (2019 ). In agreement with the importance of and in support of employing a social justice framework in developmental science, we offer theoretical and methodological options to advance each element. The options we describe are aimed at centering the humanity of AABM in the study of their development.